Effects of low-strength ultrasonication on dark fermentative hydrogen production: Start-up performance and microbial community analysis. (1st June 2018) - Cho, Si-Kyung; Jeong, Min-Wook; Choi, Yun-Kyu; Shin, Juhee; Shin, Seung Gu
Highlights: Low-strength ultrasonication enhanced bio-hydrogen production by dark fermentation. Effluent recirculation also affected hydrogen production performance. Ethanoligenes, Aeromonas and Clostridium were assumed as key H2 producers. Some Clostridium spp. responded differently upon ultrasonication treatment. Abstract: Our previous studies have demonstrated the positive impacts of low-strength (LS)-ultrasonication on biological methane production via anaerobic digestion. In this study, the effects of LS-ultrasonication and effluent recirculation on dark fermentative hydrogen production using upflow anaerobic sludge blanket reactor were investigated. Significant increase in hydrogen (H2 ) yield (up to 0.89 mol H2 /mol hexose) was observed under LS-ultrasonication conditions. This enhanced H2 yield seems to be associated with the decrease in dissolved H2 concentration via a degassing effect, as evident from increased H2 content (up to 20%). Effluent recirculation alone led to positive effects. However, applying both LS-ultrasonication and effluent recirculation decreased H2 yield compared to the trial with only LS-ultrasonication (0.89–0.72 mol H2 /mol hexose), possibly due to the cumulative shear stress and sludge bed expansion above the ultrasonication zone. Microbial community analysis revealed that the presence/absence of LS-ultrasonication and/or effluent recirculation significantly affected the microbial communities. Ethanoligenes cloacae, Aeromonas hydrophila and Clostridium pasteurianum were identified as principal H2 producers under the LS-ultrasonic conditions, while C. butyricum, the most commonly reported H2 producer, was more abundant in the controls. The energy balance of the LS-ultrasonication system was evaluated and future research directions were suggested.